ROLES OF A TEACHER IN THE CLASSROOM - Kadirova Dilfuza Alisherovna (Galaxy International Interdisciplinary Research Journal, 2024)
Teachers play vital roles in the lives of the students in their classrooms. Teachers are best known for the role of educating the students that are placed in their care. Beyond that, teachers serve many other roles in the classroom. Teachers set the tone of their classrooms, build a warm environment, mentor and nurture students, become role models, and listen and look for signs of trouble.